Guar Gum as an Edible Coating for Enhancing Shelf-Life and Improving Postharvest Quality of Roma Tomato (Solanum lycopersicum L.) - X. Ruelas-Chacon; J. C. Contreras-Esquivel; J. Montañez; A. F. Aguilera-Carbo; M. L. Reyes-Vega; R. D. Peralta-Rodriguez; G. Sanchéz-Brambila (Journal of Food Quality)
There exists an increasing interest from consumers and scientific community in developing edible-natural-biodegradable coatings to replace commercial wax-based coatings for maintaining postharvest quality of vegetables. In this work, the effectiveness of guar gum coating on various quality characteristics of Roma tomato at 22±2°C over a 20 d storage period was investigated. Tomatoes were covered with a 1.5% guar gum coating plasticized with glycerol at 30% and stored at 22±2°C and 40% RH for 20-d. Tomatoes covered with edible coating significantly enhanced firmness and reduced weight loss, delayed changes on soluble-solids-content, retarded loss of total acidity, and decreased respiration rate compared with uncoated-control fruit. Sensory analysis by trained panelists revealed that the use of the edible coating influenced the acceptability of tomatoes. There were significant differences on the scores given by panelists when comparing the coated and uncoated tomatoes. It was concluded that guar gum affected favorably the physicochemical, microbial, and sensorial quality properties of Roma tomato and therefore could be beneficial in delaying the ripening process at 22±2°C.